Kształcenie na odległość a rozwój kompetencji cyfrowych uczniów i ich rodziców w świetle wyników badań – w kierunku nowej szkoły - Gop, Aneta; Jaskulska, Sylwia (Studia Edukacyjne, 2020)
The topic of the article is students’ and their parents’ digital competences development during the COVID- 19 outbreak in Poland and distance learning. The text show results of two longitudinal studies: a qualitative one conducted on a group of parents of school-age children (N = 89), and a quantitative one, with two research groups: parents of school-age children and students aged 15-18 (various N). Parents who were providing or supporting children’s education during distance learning experienced digital competencies development. The main change has occurred in four areas: (1) information and data exploitation, (2) communication and (less frequently) collaboration, (3) digital content creation, and (4) problem-solving. Learning supported with digital technologies in the group of students did not change significantly, the level of digital competences remained basically at the same level, which can be explained by the high initial level of expertise. The experiences of distance education and the absent areas of the development of digital competences indicate the directions that future, modern education may follow.